2018
DOI: 10.1016/j.pmedr.2017.12.007
|View full text |Cite|
|
Sign up to set email alerts
|

Acculturation and dietary intake pattern among Jamaican immigrants in the US

Abstract: Information on dietary intakes of Jamaican immigrants in the United States is sparse. Understanding factors that influence diet is important since diet is associated with chronic diseases. This study examined the association between acculturation, socio-cultural factors, and dietary pattern among Jamaican immigrants in Florida. Jamaican persons 25–64 years who resided in two South Florida counties were recruited for participation. A health questionnaire that assessed acculturation, dietary pattern, and risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…However, few studies have documented dietary changes after migrating to the U.S. [ 46 51 ], or how these changes may affect taste liking [ 52 ]. Immigrants may retain their sweet liking developed in their home countries, as has been observed with other dietary habits [ 53 55 ]. Therefore, comparing immigrants vs. U.S.-born individuals of similar ancestry backgrounds may help inform whether environmental differences during early childhood affect sweet-liking status.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have documented dietary changes after migrating to the U.S. [ 46 51 ], or how these changes may affect taste liking [ 52 ]. Immigrants may retain their sweet liking developed in their home countries, as has been observed with other dietary habits [ 53 55 ]. Therefore, comparing immigrants vs. U.S.-born individuals of similar ancestry backgrounds may help inform whether environmental differences during early childhood affect sweet-liking status.…”
Section: Introductionmentioning
confidence: 99%
“…Migration and acculturation are associated with risks of chronic disease patterns. 1,2 Most epidemiological studies have shown that South Asians living in western countries have a higher risk of cardiovascular disease (CVD) as compared to local population. 2,3 Pakistan is one of the largest countries in South Asia, with a population of 180 million.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have documented dietary changes after migrating to the U.S. [30][31][32][33][34][35] , or how these changes may affect taste liking 36 . Immigrants may retain their sweet liking developed in their home countries, as has been observed with other dietary habits [37][38][39] . Therefore, comparing immigrants vs. U.S.-born individuals of similar ancestry backgrounds may help inform whether environmental differences during early childhood affect sweet-liking status.…”
mentioning
confidence: 99%